Burnout in U.K. Prison Officers: The Role of Personality. (December 2017) - Lovell, Brian; Brown, Rebecca
The study assessed the role of personality on burnout in prison officers. About 120 U.K. prison officers completed questionnaires assessing three dimensions of burnout, the "big five" personality variables, and locus of control. Neuroticism predicted emotional exhaustion and personal accomplishment, and locus of control predicted all burnout dimensions. Prison officers higher in neuroticism and with an external locus of control might be at greater risk for burnout. Future studies might examine whether stress-management interventions alleviate officer burnout, with particular attention to officers whose personality profile places them "at risk."